ANALISIS MANAJEMEN SUMBER DAYA MANUSIA PADA KOPERASI KARYAWAN TIRTA DHARMA KHATULISTIWA PDAM KOTA PONTIANAK - Bella Arista; Maria Ulfah; Bambang Genjik Sumartono (Universitas Tanjungpura, 2022)
Based on and discussion of this research, it is known that: (1) Human Resource Development Strategy by Tirta Dharma Employee Cooperative, with motivation and training on the job and off the job. (2) The obstacles faced in developing Human Resources by the Tirta Dharma Khatulistiwa PDAM Pontianak City Employee Cooperative are educational background, constraints, and cost constraints faced by the Employee Cooperative. (3) Solutions to deal with obstacles in human resource development by the Tirta Dharma Khatulistiwa PDAM Employee Cooperative with a focus on implementing development programs and motivating employees to improve their performance.